KAJIAN YURIDIS TENTANG PELAKSANAAN PERALIHAN HAK ATAS TANAH MILIK YAYASAN - CASHIN FITRIADY SETIAWAN (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Muhd Yamin, SH, MS, CN2. Notaris Dr. Suprayitno, SH, MKn3. Dr. T. Keizerina Devi A, SH, CN, MHum A foundation as an independent legal subject can take legal actions such as buying and selling. The transfer of the assets belonging to a foundation, in this case, land and building, still finds impediment in its process at the Land Office. Land Office still argues that, if the transfer goes on, it will violate Article 5 paragraph 1 of the Foundation Law. This thesis employs the normative juridical research method which is analytically descriptive. The data used to answer the research problems are secondary data. The results of the research demonstrate that, the property of the foundation is obliged to be used in accordance with the purpose and objectives of the foundation and if it is dissolved, according to Article 68 in the Law No. 28/2004 on the Amendment to the Law No. 16/2001 on Foundation, all assets shall be handed over to another foundation which shares similar purpose and objectives.Keywords: Exercise, Transfer, Rights over Land, Foundation